(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article aims to provide an in-depth analysis of the usage of prepositions in English and Uzbek languages. Prepositions play a crucial role in indicating relationships between words and phrases in a sentence. By comparing and contrasting the prepositional systems of these two languages, we can gain a better understanding of their similarities and differences, shedding light on the challenges faced by learners and translators.